The education index in the context of sustainability: Thermo-economic considerations - Grisolia, Giulia; Fino, Debora; Lucia, Umberto (Frontiers in Physics, 2022)
Sustainable development requires new technical solutions to be realized, due to the new approach to production, consumption, and management of resources. These technologies also require technical skills from workers and citizens. These technical abilities are mostly based on the knowledge of mathematics and sciences, acquired during schooling years. In this study, we develop a thermo-economic analysis of sustainable development in relation to the needs of mathematical and technical skills of future workers. To do so, the Education Index is considered to improve it toward a measure of the technical abilities of young people, maintaining its present social meaning of preventing child exploitation. The result is an improvement of the Thermodynamic Human Development Index, by introducing the OECD-PISA assessment, to allow the decision makers to analyze their policies, based on a more comprehensive vision of the present, to better design the future. Finally, we point out the need to focus public policies on the continuous stimulus of intellectual reasoning and on problem-solving-based education to develop the processing capacity and foster the creative capabilities of the younger population that builds the backbone of the future workforce.